A randomized double-blind placebo-controlled multicenter trial of Bushen Yisui and Ziyin Jiangzhuo formula for constipation in Parkinson disease. Issue 28 (10th July 2020) - Jin, Zhaohui; Liu, Zhengtang; Kang, Lei; Yang, Aoran; Zhao, Hongbo; Yan, XiaoYan; Zhang, Tianqing; Gao, Lei; Liu, Aixian; Fang, Boyan
Abstract: Introduction: Constipation is a common nonmotor symptom of Parkinson disease (PD). Constipation can also impact patient's quality of life. Chinese herbal medicines have been used for the treatment of constipation in PD. This trial will evaluate the efficacy and safety of a Chinese herbal formula Bushen Yisui and Ziyin Jiangzhuo (BYZJ) for the treatment of constipation in PD. Methods and analysis: This randomized, double-blind, placebo-controlled, multicenter clinical trial will involve 4 hospitals in Beijing, China. The study will aim to recruit 90 PD patients with constipation between 30 and 80 years-of age with a score of 1 – 4 on the Hoehn and Yahr scale. Once recruited, Patients will be randomized into a BYZJ group or a placebo group in a 2:1 ratio. The trial will include a 1-week run-in period, a 4-week double-blind treatment period, a 4-week and a 12-week follow-up period. All patients will be educated about PD-related constipation during the run-in period. BYZJ granules and simulated granules will be administered twice daily for 4 weeks to the BYZJ group and the placebo group respectively. Assessments will be performed during run-in period, before the start of treatment (baseline, week 0), and at 4, 8, and 16 weeks. The primary outcome will be measured with the Constipation Severity Instrument, and secondary outcomes will be evaluated with the Patient Assessment of Constipation Quality of Life questionnaire, Bristol Stool Form Scale, Movement Disorders–Unified Parkinson Disease Rating Scale, Nonmotor Symptoms Scale, PD Sleep Scale, Parkinson Fatigue Scale-16. Laxative use (dose and frequency) will also be recorded. Intention-to-treat and per-protocol set analyses will be used to compare symptom improvement between the 2 groups. Any adverse events will be recorded. Discussion: If found effective and safe, BYZJ formula will be one of Chinese herb to treat constipation and even other nonmotor or motor symptoms in PD patients. The results will sustain the broader use of BYZJ formula in PD.